PROFESSIONAL TRAINING OF TEACHERS FOR SOCIAL AND PEDAGOGICAL ACTIVITY: PROGRESSIVE WORLD PRACTICES - Budnyk, Olena; Nikolaesku, Inna; Atroshchenko, Tetiana; Shevchenko, Antonina; Chinchoy, Alexander; Yatsyna, Svitlana; Zobenko, Nataliia (Revista Inclusiones, 2020)
The article highlights current issues in training of social and educational professionals. The best experience of different countries on the development of social skills and abilities of children and youth, providing psychological and pedagogical support in crisis situationsis presented. It was found out that the organization of the system of juvenile social and pedagogical assistance is based on the territorial principle, so training of social professionalsis carried out at the state, local and municipal levels. Practice-oriented professional training of social workers in higher education institutions is emphasized. It was found out that in some countries (Canada, USA, France, Poland, Switzerland, Greece) more than half of students’ study time they are engaged practicing in inclusive and special schools, boarding schools, adoption and care centers, school education centers, student employment offices in dormitories, social protection services, youth shelters, etc. The authors also have described the experience of specialist training –teachers-animators for the organization of meaningful leisure of socially disadvantaged children and adolescents. The progressive experience of training of qualified specialists to work with children with special educational needs is presented.